The Indians : histories of a civilization - Devy, G. N., 1950-; Korisettar, Ravi; Joseph, Tony (Aleph Book Company, 2023)
The Indians is one of the most ambitious projects yet undertaken to map the origins, evolution, and present-day reality of India's civilization and people. Written by over one hundred of South Asia's foremost scholars and domain experts, the essays in the book cover a period of some 12,000 years-from the last Ice Age to the twenty-first century. The book is divided into seven sections. The first part looks at the evolution of humans in South Asia through the lens of the early 'Indian' population, their migrations, and the climate. The second part focuses on the emergence of different civilizations in the region through the domestication of plants and animals and other factors and how these civilizations eventually begin to decline. The third part discusses the languages and philosophies that defined ancient India-Buddhism, Jainism, Sanskrit, Indo-Iranian languages, and Pali literature, among others. The fourth part is a detailed study of society and culture in various geographical regions--the North, South, Northeast, the Deccan, East, and West India. The fifth part looks at the advent of colonialism and its impact on the country's economy, social fabric, and knowledge systems. The sixth part looks at Adivasi movements, Ambedkarite politics, Gandhian resistance, and other events that would come to form the bedrock of the independent republic. And, finally, the seventh part looks at contemporary India--the workings of the Constitution and urbanism, liberalization, and other aspects of the modern Indian experience. Taken together, the essays in the book provide remarkable insights into Indian history and society--Front jacket flap.